The supervision and multi-sectoral guarantee mechanism of the global marine sulphur limit—assessment from Chinese shipping industry - Liu, Xiaofei (Frontiers in Marine Science, 2022)
To significantly reduce sulfur oxides emissions from fossil fuel-powered ships, reduce air pollution in ports and slow ocean acidification, the International Maritime Organization (IMO) has imposed the new 0.50%m/m limit (reduced from 3.50%m/m in the past) on sulphur in ships’ fuel oil. This has given rise to a host of issues regarding fuel replenishment operations, safe operation management, maritime regulation, and coordinated governance of air and climate. In response to ocean acidification and climate change, regulations on the use of low-sulfur oil or alternative fuels by ships greatly reduce sulfur oxide emissions, but have no significant impact on reducing greenhouse gas emissions. In fact, the refining process for low-sulfur fuels and the use of the gas cleaning system on ships both increase energy consumption and carbon dioxide emissions. To ensure the decarbonization process of shipping industry, there is an urgent need for a conceptual change in global ocean governance so as to promote the coordinated governance of air pollution and climate change. China’s conception of “a maritime community with a shared future” provides a new model for global ocean governance. The Chinese government has formulated regulations at different levels to promote the coordinated management of atmospheric pollutants and greenhouse gas emissions. Regarding supervision of sulfur oxide emissions from ships, this study proposes to build a multi-department collaborative supervision mechanism from marine fuel life cycle to enhance sulfur oxide monitoring and risk control capabilities. Specific measures of the proposed supervision mechanism include: the joint supervision of compliant fuel supply, the compliant fuel information disclosure platform, a joint law enforcement mechanism for atmospheric pollution, the ability of intelligent ship exhaust monitoring, and the construction of port power infrastructure.